(untitled) (Al-Academy, 2025)
The sciences of Topology consists of the sciences of engineering, physics, and all the sciences of mathematical engineering. In fact this science means the study of the location of an object in relation to other shapes. Absolutely this science is aware of the study of shapes without in terms of their transformation through tides and softness without losing their qualitative properties. Topology is also called the engineering of rubber surface. The rubber sheets on the basis in which these shapes are topologically equivalent as long as the rubber sheet is not torn or fragmented, in addition that the square is equivalent to the circles from topological view point. In the same way a cube is comparable to a sphere. In fact the cup from which we drink is just like a swimming pool, especially in its spatial and formal spaces that are characterized by continuity and infinity. Therefore, we can say that this study focuses on integration between this science (rubber geometry of shapes and spaces) and the performing arts especially theatrical art